Unwaged Posts in UK Universities: Controversies and Campaigns - Kirsten Forkert; Ana Lopes (tripleC: Communication, Capitalism & Critique)
This article examines unwaged posts at UK universities, using recent examples of advertised job posts. While unpaid work is common in the UK higher education system, unwaged posts are not. The posts under scrutiny in this article differ from traditional honorary titles as they target early career academics, who are unlikely to have a paid position elsewhere, rather than established scholars. The article contextualizes the appearance of these posts in a climate of increasing marketization of higher education, entrenching managerialism in higher education institutions, and the casualization of academic work. We also discuss resistance to the posts, arguing that the controversy surrounding unpaid internships in the creative industries created a receptive environment for resisting unwaged posts in academia. We analyze the campaigns that were fought against the advertisement of the posts, mostly through social media and the University and College Union. We explore the tactics used and discuss the advantages and limitations of the use of social media, as well as the role of trade unions in the campaigns against these posts, and we reflect on what future campaigns can learn from these experiences.